Single-molecule two- and three-colour FRET studies reveal a transition state in SNARE disassembly by NSF - Sudheer K. Cheppali; Chang Li; Wenjing Xing; Ruirui Sun; Mengyi Yang; Yi Xue; Si-Yao Lu; Jun Yao; Shan Sun; Chunlai Chen; Sen-Fang Sui (Nature Communications)
Abstract SNARE (soluble N-ethylmaleimide sensitive factor attachment protein receptor) proteins are the minimal machinery required for vesicle fusion in eukaryotes. Formation of a highly stable four-helix bundle consisting of SNARE motif of these proteins, drives vesicle/membrane fusion involved in several physiological processes such as neurotransmission. Recycling/disassembly of the protein machinery involved in membrane fusion is essential and is facilitated by an AAA+ ATPase, N-ethylmaleimide sensitive factor (NSF) in the presence of an adapter protein, α-SNAP. Here we use single-molecule fluorescence spectroscopy approaches to elucidate the chain of events that occur during the disassembly of SNARE complex by NSF. Our observations indicate two major pathways leading to the sequential disassembly of the SNARE complex: one where a syntaxin separated intermediate state is observed before syntaxin disassembles first, and a second where Vamp disassembles from the other proteins first. These studies uncover two parallel sequential pathways for the SNARE disassembly by NSF along with a syntaxin separated intermediate that couldn’t be observed otherwise.